Who should participate in health care priority setting and how should priorities be set? Evidence from a Portuguese survey - Botelho, Anabela (2013)
This research was partially funded by Fundac ̧ão para a Ciên-cia e Tecnologia (FCT) through the Applied MicroeconomicsResearch Unit (NIMA) strategic project with reference PEst-OE/EGE/UI3181/2011